Application of the Water Service Sustainability Index to water services in sub-Saharan Africa: the case studies of eight councils in the Southern region of Cameroon (Central Africa). (18th January 2022) - Mvongo, Victor Dang; Defo, Célestin; Tchoffo, Martin
Abstract: The aim of this article is to assess the sustainability of rural water service in the Mvila Division (Southern region of Cameroon) in order to constructively feed the debate on the most effective ways to improve access to rural water service in sub-Saharan Africa. The methodological approach was based on the application of the Water Service Sustainability Index (WSSI) and was implemented through technical inspection of the rural drinking water supply system (RDWSS), the semi-structured interview, and a survey of 103 service providers. Results show that the sustainability performance of rural water service in the Mvila Division is poor–medium. The highest aggregate value of the WSSI was obtained in the Mvangan council (59.54%) followed by the Ngoulemakong council (47.99%), Biwong Bulu (38.53%), Efoulan (33.99%), Biwong Bane (31.51%), Ebolowa I (28.96%), Ebolowa II (28.19%), and Mengong (26.57%). Results also show that rural water service is influenced by factors such as the low pricing of rural water service, climate risk, the poor structuring of the maintenance chain, and the weak commitment of the municipal authorities. However, this study represents only a current snapshot of rural water service delivery conditions and should be conducted at regular intervals to track changes in overall and local conditions. HIGHLIGHTS: This study aimed to assess the sustainability of rural water service in the Mvila Division, Southern region of Cameroon. The methodological approach was based on the application of the Water Service Sustainability Index. Findings suggest that the community-based management is not an effective means of delivering rural water services. Graphical Abstract